An investigation into the detection of the pulse in conscious and anaesthetized dogs. (November 2022) - Dagnall, Clare; Wilson, Helen; Khenissi, Latifa
Abstract: Objectives: To record the success rate of veterinary professionals and students at identifying the pulse in conscious and anaesthetized dogs. To explore the influence of clinical experience, pulse location, anaesthesia and likely confounding variables on the success of pulse palpation. Study design: Prospective, observational, randomized study. Animals: A total of 54 client-owned dogs scheduled for general anaesthesia. Methods: For each dog, three participants (senior anaesthetist, anaesthesia resident/nurse, veterinary student/animal care assistant) attempted pulse palpation at three locations (femoral, radial and dorsal pedal pulse) in conscious and anaesthetized dogs. The time to pulse palpation was measured with a stopwatch for each attempt and data were modelled using a multivariate Cox regression survival analysis (significance p < 0.05). Results: The overall success rate of pulse palpation was 77%, with a median time of 10.91 seconds (interquartile range 9.09 seconds). Success rate was lower in conscious dogs (67%) than in anaesthetized dogs (87%). There was a 77% lower likelihood of success at the radial than at the femoral pulse [hazard ratio (HR) 0.23, 95% confidence interval (CI) 0.38–0.69, p < 0.001]. Veterinary students/animal care assistants had a 71% lower likelihood of success than senior anaesthetists (HR 0.29, 95% CI 0.22–0.39, p < 0.001). Age, weight and American Society of Anesthesiologists physical status had no significant influence. Premedication/anaesthetic drugs, heart rate or mean arterial pressure had no significant influence on the time to pulse palpation in anaesthetized dogs. The median time to palpation was less than 10 seconds for all experience groups at the femoral location. Conclusions: Palpation of the femoral location had the greatest likelihood of success with the least amount of time. Monitoring the femoral pulse during induction of anaesthesia is suggested as a method for confirming spontaneous circulation. Pulse palpation improves with clinical experience.